Pengaruh Rasio Keuangan Terhadap Return Saham pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015-2019 - Rizki Oktavia; Sri Hermuningsih; Alfiatul Maulida (Universitas Batanghari Jambi, 2022)
This study aims to examine and analyze: (1) how is the effect of the current ratio (CR) on stock returns, (2) how is the effect of debt to equity ratio (DER) on stock returns, (3) how is the effect of return on equity (ROE) on stock returns. stock returns, (4) how the influence of the current ratio, debt to equity ratio, and return on equity stimulants on stock returns. The population in this study are manufacturing companies in the various industrial sectors listed on the IDX for the 2015-2019 period. The sampling technique used purposive sampling. Based on the criteria, there are 18 samples of various industrial companies. The data analysis technique used multiple linear regression analysis using SPSS version 22. The results showed that (1) the current ratio (CR) had a positive and no effect on stock returns, (2) the debt to equity ratio (DER) had a negative and insignificant effect on stock returns, (3) return on equity (ROE) had an effect on positive and insignificant to stock returns, (4) the current ratio, debt to equity ratio, and return on equity simultaneously have no effect on stock returns.